No Associations Between Genetically Predicted Chronotype, Insomnia, Daytime Sleepiness, or Physical Activity and Acne Vulgaris: A Two-Sample Mendelian Randomization Study - Tian C (Clinical, Cosmetic and Investigational Dermatology)
Chaoqun Tian Department of Dermatology, Chongqing Yubei District People`s Hospital, Chongqing, 401120, People’s Republic of ChinaCorrespondence: Chaoqun Tian, Department of Dermatology, Chongqing Yubei District People`s Hospital, No. 23, Central Park North Road, Xiantao Street, Yubei District, Chongqing, 401120, People’s Republic of China, Tel +86 15123948801, Email 609860051@qq.comPurpose: The exact factors leading to the development of acne vulgaris are poorly understood. Besides diet, lifestyle habits like sleep and physical activity have received attention. This study explored the causal associations between genetically predicted sleep traits and exercise and acne vulgaris.Patients and Methods: The genome-wide association study (GWAS) data for sleep, physical activity, and acne vulgaris were retrieved from the FinnGen Project (1092/211,139 patients/controls) to carry out a two-sample Mendelian randomization (MR) analysis. Validation was performed using a dataset from the Estonian Biobank (34,422/364,991 patients/controls). The inverse variance weighted (IVW) method was the primary analytical method, with robustness tested using the weighted median, weighted mode, and MR-Egger analyses. Heterogeneity was tested using Cochran’s Q-test, horizontal pleiotropy using MR-Egger regression, outliers using MR-PRESSO, and driving SNPs using the leave-one-out method.Results: The results revealed that genetically predicted chronotype (OR=1.021, 95% CI: 0.786– 1.326, P=0.875), insomnia (OR=1.475, 95% CI: 0.676– 3.216, P=0.329), daytime sleepiness (OR=0.466, 95% CI: 0.046– 4.708, P=0.518), or physical activity (OR=0.990, 95% CI: 0.925– 1.059, P=0.767) were not causally associated with acne vulgaris. Cochran’s Q-test detected no heterogeneity (all P> 0.05). No horizontal pleiotropy was detected (all P> 0.05), indicating that the selected IVs met the third MR assumption. MR-PRESSO revealed no outliers. No single SNP drove the results according to the leave-one-out analysis. These results were validated through the use of additional datasets.Conclusion: Our study found no causal associations between sleep traits and physical activity and acne vulgaris. However, further research is needed to explore other potential factors and validate these results in more diverse populations.Keywords: acne vulgaris, sleep, physical activity, Mendelian randomization, causality